MICROBIOLOGICAL STUDY OF Escherichia coli O157 : H7 ISOLATED FROM BLOODY DIARRHOEA IN CHILDREN UNDER TEN YEARS OLD - باقر, هيثم (Iraqi Journal of Science, 2024)
This study enrolled 350 infants and young children , less than 10 years of age with bloody diarrhoea seeking medical advance at Al-Alwia children hospital through a period from the 1st of Jula 2001 till the end of October 2001 . The shape of bacteria on sorbitol macConkey, Routine Biochmical testes and Api 20E system were dependent in the diagnosis and identification of bacteria from the other members of Enterobacteracea family.The preparation of local-made selective media for isolation of this bacteria was preformed in our labs.Escherichia coli belong to the serotype O157:H7 was isolated from 4 patients (1.14%). The susceptability to antimicrobial agent was tested against E.coli O157:H7. All isolates were sensitive to Gentamicin , nalidixic acid, chloramphenical and Tobramycin , but resistant to Amoxcillin and Trimethoprim .